2021
DOI: 10.1186/s13102-021-00267-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of rapid weight loss in elite sambo athletes

Abstract: Background Rapid weight loss (RWL) is commonly practiced in combat sports. Both magnitude and methods used to induce RWL are largely similar among combat sports, but currently, there is no data on RWL methodology used by sambo athletes. Therefore, the aim of this study was to determine RWL procedures sambo athletes apply to lose weight rapidly. Methods The sample consisted of 199 participants, of which 132 males and 67 females who participated in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 35 publications
(19 reference statements)
0
36
2
Order By: Relevance
“…Similar findings were noted among male sambists, where senior athletes also regained more weight compared to juniors [ 16 ]. Furthermore, in the study by Drid et al [ 15 ], conducted with male and female sambo athletes, complementary results were obtained in terms of the methods and influences used during RWL. The most common methods in our study were gradual dieting and skipping meals, fluid restriction, and sauna use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were noted among male sambists, where senior athletes also regained more weight compared to juniors [ 16 ]. Furthermore, in the study by Drid et al [ 15 ], conducted with male and female sambo athletes, complementary results were obtained in terms of the methods and influences used during RWL. The most common methods in our study were gradual dieting and skipping meals, fluid restriction, and sauna use.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited data concerning RWL among sambo athletes. To date, and to the best of the authors’ knowledge, only two studies have examined the magnitude of RWL practices among sambo athletes [ 15 , 16 ]. This study used a similar database to the two previously mentioned studies, but examined different samples.…”
Section: Introductionmentioning
confidence: 99%
“…Very little in literature is present about physiological aspects of Sambo, e.g., [2,3], in particular, on lactate production during performance and on possible effects on cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…No other gender differences appeared. It should be noted that nearly 90% of sambo athletes reported engaging in rapid weight loss (Drid et al, 2021), a practice that is defined as a ∼5% weight loss achieved over 5-7 days, which can certainly contribute to overall stress as shown in previous studies (Franchini et al, 2012). The researches available on the topic have shown that the exceptional circumstances of COVID-19 pandemic resulted in worsened mental health (O'Connor et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…No other gender differences appeared. It should be noted that nearly 90% of sambo athletes reported engaging in rapid weight loss (Drid et al, 2021 ), a practice that is defined as a ~5% weight loss achieved over 5–7 days, which can certainly contribute to overall stress as shown in previous studies (Franchini et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%